Tc99m-DTPA Study to Validate an Experimental Model of Ureteral Obstruction in Rabbits: Preliminary Results - Marcelo Lopes de Lima; Rodolfo Bertti; Juliano César Moro; Fábio Coltro Neto; Ricardo Miyaoka; Adriano Fregonesi; Mariana da Cunha Lopes de Lima; Celso Darío Ramos (Advances in Urology)
Objective. To create a ureteral obstruction experimental model that can be proved through Tc99m-DTPA renal scintigraphy and histopathological studies, without causing total renal function loss. Materials and Methods. Ten New Zealand white rabbits were submitted to a surgical experiment to create a model of unilateral obstruction to urinary flow. Surgery procedure provided unilateral ureteral obstruction (left kidney) to urinary flow and posteriorly was evaluated by Tc99m-DTPA renal scintigraphy and histopathological study. Tc99m-DTPA renal study was performed to detect and quantify signs of obstruction and to evaluate renal function. Statistical analysis was performed through the Student t-test with a significance level of P<0.05. Results. Nine of the ten rabbits presented left renal unit obstruction and one nonobstructive on the Tc99m-DTPA and histopathological studies. All the right renal units, which were not submitted to surgical procedure, were nonobstructed by the studies. There was a general agreement between scintigraphy and histopathological results in both groups. Conclusion. The experimental model promoted the creation of ureteral obstruction in rabbits, confirmed by nuclear medicine scintigraphy and histopathology, and could be used in further studies to better understand urinary obstruction.